Factor Related to Nurse Performance in the in Patient Ward of the Rokan Hulu General Hospital 2017: Faktor yang Berhubungan dengan Kinerja Perawat di Ruang Rawat Inap Rumah Sakit Umum daerah Rokan Hulu tahun 2017 - Ahmad Hanafi; Filda Wahyuni (STIKes Hang Tuah Pekanbaru, 2019)
Hospital is an organizaon which is establish because of the complexity of public demands and they began to realize the importance of health. Therefore there is a demand to the hospital to give the maximal services to the public. Nursing care service in the hospital is one of determinant for the quality service and hospital presge in the public percepon. The nurses performances is become important to meet a demand of the public demand of the maximal quality service. This study aims to determine the relaonship training, leadership, supervision, movaon to the nurseâ€™s performance in the inpaent ward of the Rokan Hulu General Hospital 2017 This was a quantave study with analyc obervaonal desain and cross seconal approach. The analysis used univariate and bivariate analysis with chi-square test. Populaon were nurses at inpaent ward of the Rokan Hulu General Hospital amount 120 persons. Sample were 55 person who taken by accidental sampling. The results showed that there was a signiï¬cant relaonship between training (OR 4,25, p= 0,022), leadership (OR 4,44, p=0,019), supervision (OR 5,47, p=0,008), movaon (OR 5,14, p=0,010) It can be concluded that the nurseâ€™s performance is closely related to training, leadership, supervision, and movaon. It is recommended to the majareial of Rokan Hulu Regional Hospital to more frequent send nurses to aending the appropriate training, further improving good leadership funcons to improve nurse performance, supervision from supervisors in order to perform the task well, and need to provide movaon to the nurse in order to improve the performance of nurses.